Agromorphological characterization of biofortified cassava genotypes (Manihot esculenta) - Dzidzienyo, D.K.; Konadu, L.A.; Ifie, B.E.; Kamanda, I.; Diebiru-Ojo, E.M.; Danquah, E. (2025)
Cassava is an important food security crop and millions of people rely on it as a major source of food around the world. Cassava is a main staple in Ghana and an ideal candidate for biofortification to improve its nutritional content to mitigate malnutrition and increase food security. The objective of the study was to assess the genetic diversity of 21 biofortified cassava accessions using agromorphological descriptors to determine significant variations among the genotypes for breeding programs. The trial was carried out in a complete randomized block design with two replications at the University of Ghana, Legon. Data were collected at 3, 6, 9, and 12 months after planting. Significant differences were observed for all quantitative traits that were measured. There was a positive correlation between fresh root weight and the number of storage roots and also the number of leaf lobes and the length of the petiole. The first two principal component analyses (PCAs) explained 53.023% of the total variance. The key traits that influenced PC1 and PC2 included the total weight of commercial storage roots, leaf retention, average weight, number of storage roots, height at first branching, petiole length, and percentage of dry matter, further emphasizing the diverse traits among these genotypes and their breeding potential. Genotypes WC 2 and WC 14 made substantial contributions, while WC 15 signifies exceptional trait diversity and are promising candidates for enhancing genetic diversity in breeding programs. The dendrogram revealed phylogenetic relationships among the cassava germplasms, forming two main groups and subgroups. This study revealed substantial phenotypic diversity, providing a foundation for future breeding programs to improve food and nutrition security.